O primeiro inventário de bens da Catedral de Mariana (1749-1753): edição e glossário terminológico - Marcus Vinícius Pereira das Dores (2019)
This study aims at the analysis and the facsimile and diplomatic editions of the Primeiro Inventário de bens da Catedral de Mariana manuscript. The document corresponds to the first section of the Livro de Inventário da Catedral de Mariana - a document considered by UNESCO as a documentary Heritage of Humanity. The manuscript is an inventory, which was written between 1749 and 1753, and presents detailed information about the Mariana Cathedral's assets from the first Minas Gerais bishopric, including those which came from Lisbon as required by the first diocese's bishop. We also aim to create a liturgical glossary with the 116 lexical items related to the religious context that are found in the manuscript. We adopted, as theoretical approaches, perspectives from Philology and Textual Criticism, Palaeography and Codicology, Lexical Sciences, and Minas Gerais' Colonial History studies. Integrating different knowledge fields is essential since our goals and the object of study are so heterogeneous. Our findings are of great importance, because, besides linguistic and historical relevance, they also collaborate with the preservation of a unique material font.